Trade impact analysis on the profit and loss of agroecosystem service value in Guangdong Province - Huang, Shaokan; Cui, Shixi; Liao, Yuantao; Han, Feng; Sun, Shuang; Wang, Shaojian (Frontiers in Sustainable Food Systems, 2024)
Due to the imbalance in the supply and demand of agricultural land, there is an increasing trend of land resources being remoted utilized across regions. Within the context of regional trade, changes in the agroecosystem service value (ESV) can be used to assess consumer responsibility. However, the embodied flow of ESV and its driving factors have been largely unexplored. This paper, utilizing the latest Chinese multi-regional input-output tables and the equivalence factor method, explores the spatiotemporal characteristics of embodied agricultural land and ESV flow between Guangdong and 30 other provinces, and further seeks to construct three types of embodied ESV models to reveal the driving factors. The findings reveal that during the process of domestic trade in goods and services, Guangdong Province has an inflow of 2.10×10 7 hm² of land from other provinces, with arable land, forestland, and grassland accounting for 25%, 61%, and 14% respectively. Guangdong's utilization of ESV is mainly dependent on external inflows, with minimal local consumption and outflows. The embodied ESV between Guangdong and other provinces is 1626.10 billion yuan, with an outflow of 325.32 billion yuan. The "Y"-shaped region consisting of the northwest, northeast, southwest, and Hainan bears significant potential ESV losses for Guangdong Province. Population growth and the intensity of ESV loss will promote the flow of cropland and forestland ESV, while economic development has a certain inhibitory effect on ESV transfer. This paper provides a new analytical perspective on issues such as the spatial distribution mismatch of land resources and ecologically unequal exchange. These insights are pivotal for promoting sustainable utilization of land resources and regional equity.